Longitudinal associations between mothers’ and fathers’ anger/irritability expressiveness, harsh parenting, and adolescents’ socioemotional functioning in nine countries - Di Giunta, Laura (Archīum Ateneo, 2020)
The present study examines parents’ self-efficacy about anger regulation and irritability as predictors of harsh parenting and adolescent children’s irritability (i.e., mediators), which in turn were examined as predictors of adolescents’ externalizing and internalizing problems. Mothers, fathers, and adolescents (N = 1,298 families) from 12 cultural groups in 9 countries (China, Colombia, Italy, Jordan, Kenya, Philippines, Sweden, Thailand, and United States) were interviewed when children were about 13 years old and again 1 and 2 years later. Models were examined separately for mothers and fathers. Overall, cross-cultural similarities emerged in the associations of both mothers’ and fathers’ irritability, as well as of mothers’ self-efficacy about anger regulation, with subsequent maternal harsh parenting and adolescent irritability, and in the associations of the latter variables with adolescents’ internalizing and externalizing problems. The findings suggest that processes linking mothers’ and fathers’ emotion socialization and emotionality in diverse cultures to adolescent problem behaviors are somewhat similar. (PsycInfo Database Record (c) 2020 APA, all rights reserved)